1976
DOI: 10.1159/000114734
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Pressure Studies in Normal Pressure Hydrocephalus and Cerebral Atrophy

Abstract: The surgical results obtained with a cerebrospinal fluid (CSF) shunt operation in 13 patients considered to be suffering from normal pressure hydrocephalus have been correlated with the findings of the constant manometric infusion test (IT) and of prolonged intracranial pressure recordings. A positive IT, high amplitude CSF pulse pressure and large transitory increases of CSF pressure during sleep seem to be useful criteria for the surgical prognosis. Ten more patients affected by primary cerebral atrophy have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…High and/or low amplitude beta waves, abnormalities in pulse amplitude and plateau or plateau-like fluctuations especially during overnight recording and REM sleep have been widely reported in the NPHS 6-9' 13,15,27,38,40,42,43,49,52,59 Additionally, some studies have reported high mean ICP similar to that found in hypertensive hydrocephalus in patients with this syndrome 3~' 38, 42. We have used the mean ICP to classify patients into active and compensated hydrocephalus.…”
Section: Discussionmentioning
confidence: 93%
“…High and/or low amplitude beta waves, abnormalities in pulse amplitude and plateau or plateau-like fluctuations especially during overnight recording and REM sleep have been widely reported in the NPHS 6-9' 13,15,27,38,40,42,43,49,52,59 Additionally, some studies have reported high mean ICP similar to that found in hypertensive hydrocephalus in patients with this syndrome 3~' 38, 42. We have used the mean ICP to classify patients into active and compensated hydrocephalus.…”
Section: Discussionmentioning
confidence: 93%
“…As a result, less blood can be shifted extracranially to accommodate the injected volume. The same mechanism explains the increase in CSF pulse pressure in adult hydrocephalus (Di Rocco et al, 1976;Foltz and Aine, 1981). Here it is the patient's heart that injects a relatively fixed volume of blood intracranially with each cardiac systole.…”
Section: Cerebral Content Of Interstitial Fluidmentioning
confidence: 90%
“…The apparently high diagnostic significance of the ICP recording appears interesting s, 12,35,36,54,55 However, the limitation of this examination to a few patients only requires further study.…”
Section: Discussionmentioning
confidence: 99%